Biomaterials surface science - Taubert, Andreas; Mano, João F.; Rodríguez-Cabello, J. Carlos (Weinheim : Wiley-VCH, 2013)
The book provides an overview of the highly interdisciplinary field of surface science in the context of biological and biomedical applications. The covered topics range from micro- and nanostructuring for imparting functionality in a top-down manner to the bottom-up fabrication of gradient surfaces by self-assembly, from interfaces between biomaterials and living matter to smart, stimuli-responsive surfaces, and from cell and surface mechanics to the elucidation of cell-chip interactions in biomedical devices.
Polymer Surfaces. Part One: Polymer Surfaces / Alexander Schulz, Stephanie Hiltl, Patrick van Rijn, Alexander Böker -- Surface-Grafted Polymer Brushes / Szczepan Zapotoczny -- Inhibiting Nonspecific Protein Adsorption: Mechanisms, Methods, and Materials / Mojtaba Binazadeh, Hongbo Zeng, Larry D Unsworth -- Stimuli-Responsive Surfaces for Biomedical Applications / Rui R Costa, Natália M Alves, J Carlos Rodríguez-Cabello, João F Mano -- Surface Modification of Polymeric Biomaterials / Aysun Guney, Filiz Kara, Ozge Ozgen, Eda Ayse Aksoy, Vasif Hasirci, Nesrin Hasirci -- Polymer Vesicles on Surfaces / Agnieszka Jagoda, Justyna Kowal, Mihaela Delcea, Cornelia G Palivan, Wolfgang Meier -- Hydrogel Surfaces. Protein-Engineered Hydrogels / Jordan Raphel, Andreina Parisi-Amon, Sarah C Heilshorn -- Bioactive and Smart Hydrogel Surfaces / J Carlos Rodríguez-Cabello, A Fernández-Colino, M J Piña, M Alonso, M Santos, A M Testera -- Bioresponsive Surfaces and Stem Cell Niches / Miguel Angel Mateos-Timoneda, Melba Navarro, Josep Anton Planell -- Hybrid & Inorganic Surfaces. Micro- and Nanopatterning of Biomaterial Surfaces / Daniel Brodoceanu, Tobias Kraus -- Organic/Inorganic Hybrid Surfaces / Tobias Mai, Katrin Bleek, Andreas Taubert -- Bioactive Ceramic and Metallic Surfaces for Bone Engineering / Carlos Mas-Moruno, Montserrat Espanol, Edgar B Montufar, Gemma Mestres, Conrado Aparicio, Francisco Javier Gil, Maria-Pau Ginebra -- Plasma-Assisted Surface Treatments and Modifications for Biomedical Applications / Sanjay Mathur, Trilok Singh, Mahboubeh Maleki, Thomas Fischer -- Biological and Bioinspired Micro- and Nanostructured Adhesives / Longjian Xue, Martin Steinhart, Stanislav N Gorb -- Cell-Surface Interactions. Generic Methods of Surface Modification to Control Adhesion of Cells and Beyond / Marcus Niepel, Alexander Köwitsch, Yuan Yang, Ning Ma, Neha Aggarwal, Deepak Guduru, Thomas Groth -- Severe Deformations of Malignant Bone and Skin Cells, as well as Aged Cells, on Micropatterned Surfaces / Patricia M Davidson, Tokuko Haraguchi, Takako Koujin, Thorsten Steinberg, Pascal Tomakidi, Yasushi Hiraoka, Karine Anselme, Günter Reiter -- Thermoresponsive Cell Culture Surfaces Designed for Cell-Sheet-Based Tissue Engineering and Regenerative Medicine / Jun Kobayashi, Teruo Okano -- Cell Mechanics on Surfaces / Jessica H Wen, Hermes Taylor-Weiner, Alexander Fuhrmann, Adam J Engler -- Electrode-Neural Tissue Interactions: Immune Responses, Current Technologies, and Future Directions / Gloria Bora Kim, Pouria Fattahi, Mohammad Reza Abidian.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed August 13, 2013).
Keywords: Biomedical materials; Surface chemistry; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biomedical materials; Surface chemistry; Biomaterial; Nanostruktur; Oberflächenchemie; Biomedical and Dental Materials; Materials biomèdics; Electronic books; Electronic books